The Correlation Between Macronutrient Intake and The Incidence of Underweight in Toddlers - Yudia Wulandari; Hardi Firmansyah; Erli Mutiara; Risti Rosmiati; Nila Reswari Haryana (Sport and Nutrition Journal, 2025)
Underweight is when a child's weight is below the average range for their age group. The prevalence of underweight toddlers in Indonesia in 2023 reached 12.9%. Underweight is directly caused by food intake. This study aims to determine the relationship between macronutrient intake and the incidence of underweight in toddlers at Posyandu Bangun Sari Indah 6. This research method uses a cross-sectional research design. The population in this study consisted of toddlers aged> 6-59 months, with a total of 135 toddlers. The technique for selecting research subjects used a purposive sample of 48 toddlers. Data collection of food intake used a 2x24-hour food recall form, and underweight data used anthropometric measurements of BB/U. The data analysis technique was descriptive, using the Spearman rank correlation test and the logistic regression test. The results showed a relationship between energy intake (p = 0.003), carbohydrate intake (p = 0.004), protein intake (p = 0.005), and fat intake (p = 0.025) with the incidence of underweight in toddlers. The logistic regression test analysis showed that energy, carbohydrate, protein, and fat intake were not significantly related to the incidence of underweight.